2018
DOI: 10.1038/s41598-018-27122-9
|View full text |Cite|
|
Sign up to set email alerts
|

Relativistic Doppler-boosted γ-rays in High Fields

Abstract: The relativistic Doppler effect is one of the most famous implications of the principles of special relativity and is intrinsic to moving radiation sources, relativistic optics and many astrophysical phenomena. It occurs in the case of a plasma sail accelerated to relativistic velocities by an external driver, such as an ultra-intense laser pulse. Here we show that the relativistic Doppler effect on the high energy synchrotron photon emission (~10 MeV), strongly depends on two intrinsic properties of the plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…As theoretically foreseen, an irradiation of plasma targets by multi-petawatt laser radiation can result in high efficiency of the laser energy conversion to the energy of gamma-ray flash [18][19][20][21][22][23][24][25][26][27][28]. Below, we present the results of multi-parametric studies of laser-target interaction for generation of bright γ-flare, aiming on parameters of ≈ 10 PW, kJ-scale laser, which will be available in the coming years.…”
Section: Introductionmentioning
confidence: 99%
“…As theoretically foreseen, an irradiation of plasma targets by multi-petawatt laser radiation can result in high efficiency of the laser energy conversion to the energy of gamma-ray flash [18][19][20][21][22][23][24][25][26][27][28]. Below, we present the results of multi-parametric studies of laser-target interaction for generation of bright γ-flare, aiming on parameters of ≈ 10 PW, kJ-scale laser, which will be available in the coming years.…”
Section: Introductionmentioning
confidence: 99%
“…The largest difference would be expected for a single laser illuminating the target from one side. By comparing the results from a recent paper considering this case [25] we see that the regimes are broadly similar but that the cascade occurs at much lower intensity in the counter-propagating laser case considered here -for single-sided illumination the target is accelerated to relativistic speeds by the laser's radiation pressure, reducing the intensity in its rest-frame [25,59] (although Doppler boosting can increase the degree of collimation of the emitted gamma-ray photons [60] and perhaps also the produced pairs, which may be advantageous for some applications). Comparison to this work suggests that if dense pair plasma production is the desired outcome of an experiment then two-sided illumination of a near-critical density plasma is the ideal choice.…”
Section: Discussionmentioning
confidence: 63%
“…2a and 2b respectively. From these figures we see that both the beams are highly divergent, although it has recently been shown that the γ-ray divergence can be substantially reduced by lowering the target mass [22]. These electrons and photons then propagate into the bulk of the target.…”
Section: Resultsmentioning
confidence: 93%